AGILE DEVELOPMENT OF THE RE-QUEST INCENTIVE-BASED SURVEY APPLICATION: ENSURING ETHICAL FAIRNESS IN DATA COLLECTION - Asoka Syukur, Pramudya; Miftach Fakhri , M.; Nirmala S, Aprilianti; Miftahul Jannah , Devi; Nurjannah, Elma; Dio Nurul Awalia, Andi (Jurnal Media Elektrik, 2025)
Low response rates in digital surveys due to survey fatigue and challenges in maintaining data quality. To develop an incentive-based survey application using the Agile method to enhance participation and data quality. The study used the Agile methodology within the framework of the Software Development Life Cycle (SDLC), focusing on iterative sprints for planning, analysis, design, implementation, and testing using the Black Box method to ensure application functionality and reliability. The "Re-Quest" application was successfully developed with key features such as survey management, an incentive calculator, and incentive redemption. The Agile method improved development flexibility and implementation efficiency. Fairness-based incentives, grounded in ethical principles of justice and equality, increased respondent responsiveness without compromising data quality. Testing results showed all application functionalities operated as designed. The "Re-Quest" application provides an innovative solution for improving participation and data quality in digital surveys through a fairness-based incentive approach, offering significant benefits for scientific research and education.